Identifying Factors Influencing Customer Satisfaction in Community Pharmacies: A Systematic Review - Widyasari, Leiren Garda; Wiedyaningsih, Chairun; Widayanti, MPH., Apt., Ph.D., Anna Wahyuni (Academic Hospital Journal, 2025)
Background: The paradigm shift from a drug-oriented to a patient-oriented approach requires health facilities to improve the quality of pharmaceutical services. Meeting customer needs and expectations can increase satisfaction and support the achievement of therapeutic goals.Objective: Conduct an in-depth analysis of the available literature to identify customer satisfaction factors towards pharmaceutical services in community pharmacies.Method: A systematic review was conducted by searching articles across three databases: ScienceDirect, Scopus, and PubMed. The search flow is described in the PRISMA Diagram. Inclusion criteria included customer satisfaction with pharmaceutical service articles and research settings in community pharmacies. Exclusion criteria included online or hospital pharmacy articles and review articles, books, theses, dissertations, and reports. Articles are assessed using the Joanna Briggs Institute's critical appraisal instrument.Result:  The findings from the nine articles revealed various factors that influence customer satisfaction, which can be categorized into intangible and tangible factors. Intangible factors include the attitude and communication of pharmacy staff, as well as consultations regarding medications and health conditions. Tangible factors include the facilities and convenience, the availability and variety of medications, prices, and customer demographics.Conclusion: The identified customer satisfaction factors can be useful to increase pharmacy customer loyalty. Thus, it can encourage customers to make repeat orders.